To give a dog a bad name to kill it – Cameroon's anti-terrorism law as a strategic framework for human rights' violations. Issue 1 (2nd January 2021) - Ashukem, Jean-Claude N.
ABSTRACT: Since the enactment of Cameroon's anti-terrorism law in 2014, the government has embarked on systemic violation of fundamental human rights and freedoms. In this article, I identify and examine instances of human rights violation perpetrated by the government of Cameroon through the anti-terrorism law. I argue that the law is increasingly being used as a strategic framework to suppress the exercise and enjoyment of fundamental rights in Cameroon. I specifically argue that the Military Court's interpretation and application of the law against the rights to strike and freedom of expression, for example, are wrong and unconstitutional. Accordingly, the law is an anathema to human rights and could rightly be qualified as the new law on repression of fundamental rights. There is a need for the government of Cameroon to amend the law such that it reflects its international human rights' commitments.